The features of coping in patients with cosmetic problems and disharmonious self-attitude with heightened self-esteem - Юдін, Михайло Анатолійович (ScienceRise: Medical Science, 2016)
Aim of research was to reveal the features of stress-overcoming behavior of cosmetic patients with disharmonic self-attitude and heightened self-esteem. Contingent and methods. The research was carried out on the base of medical center “CA-CLINIC” (city Kyiv) during 2014 – 2016. The testing included 188 women, who asked for cosmetic help. The interrogated were divided in groups on the base of criterion of self-attitude: the main group included persons with disharmonic type with tendency to heightened self-esteem (MG, n=82), the control group included women with harmonic type (CG, n=96). Psychodiagnostic instrument was the questionnaire of the “Ways of overcoming behavior” by R. Lazarus and S. Folkman. Results. For the women with disharmonic type of self-attitude and heightened self-esteem was typical the following features. The main factors of stress-overcoming behavior were confrontation and search for social support, less expressed were distancing, self-control, responsibility, planning and least expressed was the positive reassessment. The higher levels of confrontation and distancing and the lower one of positive reassessment comparing with women with harmonic type of self-attitude were revealed. The coping-profile was manifested by impetuosity, active behavior at solving problems that could lose the character of purposefulness, rigid vindication of interests, difficulties in re-formulation of personal settings, indisputability of own position, need of involvement of social resources for attraction of attention, information, active help, emotional inclusion and devaluation of problem, rationalization, ability to control oneself, to plan. The feature of coping was the growth of tension of non-adaptive and conventionally adaptive and decrease of adaptive forms of coping, presence of strategies of stress-overcoming behavior, opposite by content that totally conditioned the decrease of effectiveness in overcoming of stress. Conclusions. The features of stress-overcoming behavior in women with disharmonic self-attitude and heightened self-esteem indicated the necessity of psychic correction within the complex program of medical-psychological help